Adaptive Strategies of MSMEs in Transforming Challenges Into Opportunities During the COVID-19 Pandemic Era - Suyitno, Imam (International Journal of Humanities, Education, and Social Sciences, 2025)
The world has been grappling with the waves of the COVID-19 pandemic since 2020, and to this day, no accurate prediction has been made regarding its end. Indonesia is no exception, with uncertainty still looming over the resolution of this global crisis. However, recent data indicate a general decline in cases, including infection rates and mortality due to COVID-19. The pandemic has had a profound impact across all aspects of life, including politics, economics, society, education, and national security. This unprecedented humanitarian disaster was unforeseen by anyone. Economically, the pandemic has caused significant disruptions, affecting both state revenues and individual incomes, particularly for those in the private sector. Large-scale and small-scale businesses alike have experienced drastic declines in earnings, a situation unparalleled in prior times. Consequently, many companies, regardless of size, have been compelled to downsize their workforce or enforce layoffs, leading to an inevitable rise in unemployment rates within society. The economic ramifications of this pandemic highlight the urgent need for adaptive strategies to address these challenges.